مساهمة الأدوات الحديثة لمراقبة التسيير في تقييم الأداء الاستراتيجي للمؤسسة - بن عمر حمزة (Universty Of El-oued جامعة الوادي, 2024)
الملخص: تناولت هذه الدراسة موضوع دور الأدوات الحديثة لمراقبة التسيير(ABC , TB, BSC )، ومدى مساهمتها في تقييم الأداء الإستراتيجي للمؤسسة، من خلال دراسة عينة من المؤسسات الجزائرية والأجنبية على ثلاث مستويات، المؤسسات الكبرى (HALLIBURNTON،SONATRACH )، المؤسسات المتوسطة (G.M.S , SARL BAKKAR)، المؤسسات الصغرى ( SARL SOUFIA, Biscofruits )، وقد شملت عينة الدراسة 137موظف من مستعملي الأدوات الحديثة لمراقبة التسيير داخل المؤسسات، حيث استخدمت هذه الدراسة المنهج الوصفي عن طريق استقراء الدراسات الأبحاث الكتب والمقالات العربية والأجنبية، وفي الجانب التطبيقي اعتمدنا في هذه الدراسة على إجراء المقابلات، والاستبيان، ووثائق المؤسسات، من اجل التعرف علىواقع العلاقة التأثيرية بين الأدوات الحديثة وتقييم الأداء الإستراتيجي؛ ولتحليل الاستبانة تم الاعتماد على التحليل الإحصائي الوصفي باستخدام برنامج، SPSS V22وتحليل الانحدار البسيط والمتعدد وتحليل التباين الأحادي، وقد توصلت هذه الدراسة إلى أهم النتائج التي توصلنا إليها هو أنه يوجد إستخدام الأبعاد الخمسة المدمجة للأدوات الحديثة (ABC , BSC) لجميع مؤسسات محل الدراسة، وأن هذه الأخيرة ترتكز على مؤشرات معينة من أجل تقييم أدائها، وتختلف من حيث الأهمية والاعتماد عن تلك المتوصل إليها في الدراسات السابقة، كما أظهرت النتائج أن البعد المالية يحمل الصدارة في الأثر على تقييم الأداء الإستراتيجي للمؤسسات يليه كل من بعد العملاء والبعد البيئي، أما باقي الأبعاد - العمليات الداخلية، التعلم والنمو- فإنها أقل أثر ودلالة إحصائية لاستخدام الأدوات الحديثة لمراقبة التسيير في تقييم أداء المؤسسات الاقتصادية بالجزائر محل الدراسة. وقد قدمت الدراسة عدداً من التوصيات من أبرزها تعزيز معرفة أصحاب الشركات والمؤسسات الاقتصادية لأهمية تطبيق الأدوات الحديثة لمراقبة التسيير عموما، وبصفة خاصة BSC وربطها بنظام ABC، من خلال قيام الجمعيات المحاسبية والمهنية بعقد مؤتمرات ووضع برامج تعليمية وندوات علمية، لاتخاذ خطوات فورية نحو تبني تطبيق نظام ببطاقة الأداء المتوازنBSC للاستفادة من مزاياه كأداة لقياس وتقييم الأداء الإستراتيجي، وكذا نظام التكاليف على أساس الأنشطةABC لما لها من فوائد ومزايا متعددة تخدم بها الإدارة الحديثة لمواجهة التحديات والتغييرات البيئية المحيطة بها، يكون ذلك عبر إعادة تشكيل الثقافة التنظيمية، وتهيئة الظروف اللازمة لتفعيل عملية التطبيق. Résumé :فرنسية أو انجلزية The contribution of modern management control tools to the evaluation of the strategic performance of the institution A study of a sample of economic institutions-- Abstract: This study addressed the issue of the role of modern management control tools (ABC, TB, BSC), and the extent of their contribution to the evaluation of the strategic performance of the institution, through the study of a sample of Algerian and foreign institutions on three levels, large institutions (HALLIBURNTON, SONATRACH), medium enterprises (G.M.S, SARL BAKKAR), small enterprises (SARL SOUFIA, Biscofruits), and the study sample included 137 employees who used modern tools to monitor management within institutions, as this study used the descriptive approach by extrapolating studies, research, books, Arabic and foreign articles, and in the practical side, we adopted these The study conducted interviews, questionnaires, and institutional documents, in order to identify the reality of the effective relationship between modern tools and strategic performance assessment; To analyze the questionnaire, the descriptive statistical analysis was relied on using the program, SPSS V22, simple and multiple regression analysis, and one-way analysis of variance. The latter are based on certain indicators in order to evaluate their performance, and they differ in terms of importance and dependence from those reached in previous studies. The results also showed that the financial dimension takes precedence in the impact on the strategic performance evaluation of institutions, followed by the customer dimension and the environmental dimension. As for the rest of the dimensions - Internal processes, learning and growth - it is less effective and statistically significant for the use of modern management control tools in evaluating the performance of the economic institutions in Algeria under study. The study presented a number of recommendations, most notably enhancing the knowledge of the owners of companies and economic institutions of the importance of applying modern management control tools in general, and in particular the BSC and linking them to the ABC system, through accounting and professional associations holding conferences and developing educational programs and scientific seminars, to take immediate steps towards adopting the application of the system With the Balanced Scorecard (BSC) to take advantage of its advantages as a tool for measuring and evaluating strategic performance, as well as the costing system based on ABC activities, because of its multiple benefits and advantages that serve modern management to meet the challenges and environmental changes surrounding it, by reshaping the organizational culture, and creating the necessary conditions to activate the application process .
أطروحة دكتوراه تخصص: تدقيق ومراقبة التسيير في العلوم الاقتصادية والتجارية وعلوم التسيير
Keywords: الأدوات الحديثة لمراقبة التسيير؛ نظام التكاليف على أساس الأنشطةABC؛لوحة القيادة TB؛بطاقة الأداء المتوازن BSC؛الأداء الإستراتيجي; modern management control tools; costing system based on activities ABC; TB dashboard; BSC Balanced Scorecard; strategic performance.